Diagnostic Value of Fuld Object Memory Evaluation on Dementia after Stroke - Bo CHEN; Jihua YU; Fangyuan XU (康复学报)
Objective:To explore the diagnostic value of Fuld Object Memory Evaluation (FOME) on dementia after stroke.Methods:A total of 100 patients with vascular dementia (the case group) were tested by the FOME and Mini-Mental State Examination (MMSE) with 100 healthy subjects who did physical examination in the same period of our hospital (the control group). The FOME involved direction recognition, object naming, visual naming, first, second, and last recall and the final memory. The MMSE tested the orientation, immediate recall, calculating ability and attention, delayed recall, naming, retelling orally, language comprehension, reading comprehension, language expression and visuospatial ability. The comparison was done on the results of the tests and the background conditions, such as gender, age, education and residence; and it was also analysed by ROC curve with the diagnostic value of the FOME on vascular dementia, calculating the diagnostic sensitivity, specificity and Jordon index, and comparing with the results of MMSE.Results:There was no statistical significance between the two groups (P> 0.05) in aspects of gender, age, educational level and residence; while the differences between test results of the two groups were statistically significant (t=14.707 and t=13.486, P< 0.001), and the scores of the case group were lower than those of the control group. As the ROC curve shown, the optimal cutoff value of MMSE was 27, that of the FOME was 14, the sensitivity of MMSE was 63.98%, the specificity of MMSE was 94.17%, and those of the FOME were 63.45%and 95.48%, respectively.Conclusion:The FOME can be equivalent to the MMSE in the diagnosis of dementia after stroke; with advantages in no considering education background and age, which can be expected to have a wider clinical application.